Bina Iman Remaja Perempuan Katolik di Asrama Maria Lordes SMK Muktyaca Ende - Lelboy, Viktoria (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Due to the mentors' conflicting responsibilities, the teenage girls at the Maria Lordes Ende dormitory struggle with the absence of regular spiritual supervision. As a result, one of the immediate fixes is for them to join the mentoring team at SMK Muktyaca Ende's Maria Lordes Dormitory in addition to being the PKM implementers. Since Catholic youth are the Church's hope and agents of renewal due to their innate qualities of being vivacious, creative, dynamic, sympathetic, critical, and risk-taking, it is imperative that youth faith development mentoring be included in the Congregation's annual programs. Spending time with young people also exposes them to circumstances and technology advancements that significantly test their spirituality and personalities. Therefore, in order to assist these young women, it is essential to provide careful consideration to needs like conceptual and continuous advice, which will help these teenagers avoid making snap judgments that could harm themselves. The target audience for this community service project is Catholic teens living in the Maria Lordes hostel at SMK Muktyaca Ende. Helping young women value life as women and participate in spiritual activities is the aim of this activity. To rekindle excitement from tedium and monotony during the process, a qualitative participative method is employed, which includes lectures and basic practical exercises. This program aims to teach young ladies to value their femininity and participate in spiritual activities. The technique is a qualitative participatory approach that uses lectures and basic hands-on activities to rekindle interest during the activities and break monotony. Thus, the end effect is that Catholic adolescent girls develop greater self-awareness, explore their inner selves more deeply, love and accept themselves, and live out their spirituality every day.